Les assistantes familiales, travailleuses du care : le sensible comme éthique de la relation en actes - Nadège Séverac (Sociétés et Jeunesses en Difficulté)
This contribution is about young people protected by the child protection system, called “incasables” because they refuse all the rules, breaking and beating up until they are excluded or run away. Only some foster families, willing to take these young people to their home, manage to calm them down, showing an unknown expertise. They speak about sensibility to the other’s vulnerability and their own intention of « good » than of skills, showing an ethic of care, where what matters are the persons and their relations. When educators say their attachment to professional distance and to the respect due to the “educative contract”, referring to an ethic of justice, where what matters are principles. We propose to show why, even if they act as social work guide lines recommend, educators fail to stabilize the “incasables”. We describe how, even if they don’t act as social work guide lines recommend, foster care families manage to tame them and how they are enlightened, despite their success, the way they do is not seen and their voice remains unheard. The price of this indifference being the production of the young people’s violence.